COMPOSITION OF THE ESSENTIAL OIL OF SALVIA OFFICINALIS L., GROWN IN UZBEKISTAN - V. N. Abdullabekova; Kh.K. Bekchanov (Journal Park Publishing, 2025)
The paper presents the results of qualitative and quantitative analysis of essential oil obtained from Salvia officinalis L. by hydro-steam distillation. The essential oil obtained from given plant is a light yellow, easily mobile liquid with a characteristic specific odor. The qualitative composition and quantitative content of essential oil components were determined by GC/MS. The composition of essential oils is represented mainly by mono- and sesquiterpene compounds. The yield of essential oils of the aerial part of Salvia officinalis L. was 0.76% of the weight of air-dried raw materials. The content of monoterpene compounds was 44.00%, sesquiterpene compounds - 44.47%.
Keywords: Salvia officinalis L., essential oil, chromatograph mass-spectrometry, terpenes, State Pharmacopoeia of Uzbekistan.